Observations from Autonomous Ocean Flux Buoy 43 deployed at site L1 during the MOSAiC transpolar drift, Arctic Basin, 2019-2020 ... - Stanton, Tim; Shaw, Bill (NSF Arctic Data Center, 2023)
During the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition, four Autonomous Ocean Flux Buoys (AOFB) were set up on ice floes on the Siberian side of the Arctic Basin during October 2019 from the Academic Federov ice breaker. AOFB46 was located adjacent to the meteorology tower at the Central Observatory (CO) which was manned from the AWI (Alfred Wegener Institute) Polarstern ice breaker moored to the ice floe. AOFB43, 44, and 45 were deployed with other instrument systems at three remote sites – L1, L2 and L3, nominally 20 kilometer (km) out from the CO. The ice pack supporting the observation systems drifted across the Central Arctic toward Spitzbergen during the following 9 months. Data in this package from AOFB 44 is contained in a netCDF file with measurements of ocean variables that have been averaged onto 2-hour-long time intervals, the sample rate used for the ocean turbulence measurements. These timeseries are 1. The decimal yearday (yd) of 2019 of the ...